2018
DOI: 10.3762/bjnano.9.225
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive contact of rough brushes

Abstract: The adhesive contact between a rough brush-like structure and an elastic half-space is numerically simulated using the fast Fourier transform (FFT)-based boundary element method and the mesh-dependent detachment criterion of Pohrt and Popov. The problem is of interest in light of the discussion of the role of contact splitting in the adhesion strength of gecko feet and structured biomimetic materials. For rigid brushes, the contact splitting does not enhance adhesion even if all pillars of the brush are positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(33 reference statements)
2
5
0
Order By: Relevance
“…In the case of rough brushes where the height of pillars has an exponential probability density, similar qualitative results to Fuller and Tabor's prediction [16] were obtained, which states that the adhesive force is reduced with roughness [15]. However, in these studies [13][14][15], the pillars are rigid, which is not the case for insect or gecko feet. The flexibility may play an important role in adhesion and contact splitting.…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…In the case of rough brushes where the height of pillars has an exponential probability density, similar qualitative results to Fuller and Tabor's prediction [16] were obtained, which states that the adhesive force is reduced with roughness [15]. However, in these studies [13][14][15], the pillars are rigid, which is not the case for insect or gecko feet. The flexibility may play an important role in adhesion and contact splitting.…”
Section: Introductionsupporting
confidence: 75%
“…For a flat brush structure, it is found that the adhesive force is roughly proportional to the square root of the real contact area, meaning that adhesion is not enhanced [14]. In the case of rough brushes where the height of pillars has an exponential probability density, similar qualitative results to Fuller and Tabor's prediction [16] were obtained, which states that the adhesive force is reduced with roughness [15]. However, in these studies [13][14][15], the pillars are rigid, which is not the case for insect or gecko feet.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations